Market of tissue engineering in Canada from 2011 to 2020 - Cao, Ning Tate; Muthukumaran, Subhiksha; Chen, Xiongbiao (Frontiers in Bioengineering and Biotechnology, 2023)
This project aimed to perform a market analysis for understanding and promoting the development and commercialization of tissue engineering in Canada. We identified companies established between October 2011 and July 2020 via publicly available information and for such companies, we collected and analyzed the corporate-level information, including revenues, and number of employees and founder information. The companies assessed were mainly searched from four different industry segments, i.e., bioprinting, biomaterials, cells and biomaterials, and stem-cells related industry. Our results have demonstrated that there are twenty-five tissue-engineering companies registered in Canada. These companies generated an estimated revenue of USD $67 million in year 2020, most generated by the tissue engineering and stem-cells related industries. Also, our results shows that Ontario has the largest number of headquarters of tissue engineering companies among the provinces or territories of Canada. It is expected that the number of new products undergoing clinical trials is to be increased, based on our results regarding current clinical trials. In conclusion, tissue engineering in Canada has shown a huge growth in the past decade and is forecasted to be an emerging industry in Canada for the years to come.